Clinical profile of empyema in tertiary health care center, Hyderabad - Shah, Kalindi; Shaikh, Farhan; Poddutoor, Preetham Kumar; Kancherla, Ramesh (Indian Journal of Child Health, 2015)
Objective: Empyema thoracic is known to have a variable age group affection, causative agents and controversy regarding primary mode of management. The aim of this study was to study the epidemiology, management strategies including investigations and outcome of empyema in the children. Methods: A prospective study was done on all cases of parapneumonic empyema admitted to our hospital from February 2009 to April 2011. Diagnosis of empyema was confirmed by chest X-ray, pleural fluid analysis or radio-imaging. All children (depending on staging) were treated along with parental antibiotics and chest tube drainage either intrapleural urokinase or surgery (video assisted thoracoscopy surgery [VATS] or thoracotomy) according to British Thoracic Society guidelines. Results: Among study population, male to female ratio was 1.48:1. The most common age group affected was 1-5 years (mean 4.03 ± 3.30 years). Total 31.57% of the cultures were positive. The most common isolated organisms were Streptococci (38.9%) and Staphylococci (44.4%). Out of 57 children, 25 had Stage II of empyema while 32 had Stage III of empyema. There was a significant correlation betweenduration of illness (>7 days) and advancement in the stage of empyema (p < 0.0001). Only one child with Stage II of empyema required surgery while remaining all other (24 out of 25) were managed with thoracostomy and intrapleural injection of urokinase. Remaining 32 (18 VATS and 14 thoracotomy) patients with Stage III of empyema underwent primary surgical management. There was no significant difference in the duration of fever remission, total hospital stay or duration of IV antibiotics in children treated either with intrapleural fibrinolytics or surgical management. Overall outcome of empyema was excellent, mortality was less than 1.5%, with overwhelming sepsis. Conclusion: Staging of empyema at initiation of treatment helps in proper management of patients. Results with the use of intrapleural fibrinolytics were promising in the Stage II of empyema. As complications are very few, VATS is a safe procedure in experienced hands.